Sign up ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

Let $$a_{n,k}=\sum_{s_i \geq 1 \atop \sum_{i=1}^{n-k} s_i \leq n} \frac{2^{n}}{(2(n-\sum_{i=1}^{n-k} s_i)+1)!\prod_{i=1}^{n-k} (2s_i)! }$$ for $0 \leq k \leq n-1$. Prove for $1 \leq k \leq n-1$ that $$b_{n,k}=\sum_{l=1}^k (-1)^{k-l} \sum_{s_i \geq 1 \atop \sum_{i=1}^l s_i =k} \prod_{i=1}^l a_{n,s_i}>0.$$ Motivation and alternative formulation can be found here

share|cite|improve this question
Any chance that $b_{n,k}$ is an inclusion-exclusion summation? – Brendan McKay May 10 '13 at 6:01
Yes, it may be possible to interpret it as a inclusion-exclusion summation which would prove the positivity but I don't know how. The formula for $b_{n,k}$ comes from the condition $$\sum_{i=0}^ka_{n,i}b_{n,k-i}=0$$ – Markus May 10 '13 at 7:56
Forgot a $(-1)^i$ in the formula – Markus May 10 '13 at 7:57

1 Answer 1

up vote 0 down vote accepted

Found the answer on page 102 of

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.